Foodborne pathogens in Africa: Understanding Cronobacter sakazakii - Ifeanyi Michael Mazi; Helen Onyeaka; Nnabueze Darlington Nnaji (Wiley, 2023)
Abstract Cronobacter sakazakii is an emerging and opportunistic foodborne pathogen that causes severe infantile diseases, including meningitis, necrotizing enterocolitis, and septicemia. It has been reported in numerous countries around the world, including those in Africa. Although it has been isolated from food, environmental and clinical samples across Africa, the most implicated source of the C. sakazakii infection outbreaks across the globe has been the consumption of contaminated powdered infant formula. Cronobacter has many unique characteristics that contribute to its survival in harsh environments and transmission along the food chain from production to consumption. A potential foodborne disease outbreak caused by C. sakazakii can increase the overall foodborne disease burden and hinder any progress in managing the overly strained public health situation in Africa. This article presents an insight into the occurrence and prevalence of C. sakazakii infection in Africa's food environment, pointing out the transmission route along the food chain and its accompanying food safety concerns. This paper advocates for strict compliance with food safety and control measures to prevent its spread in African countries.